Recent Advances of Gold Compounds in Anticancer Immunity - Yue, Shuang; Luo, Miao; Liu, Huiguo; Wei, Shuang (Frontiers in Chemistry, 2020)
In recent years, gold compounds have gained more and more attentions in the design of new metal anticancer drugs. Numerous researches reported that gold compounds, in addition to their widely studied cytotoxic antitumor effects, reversed tumor immune escape and directly facilitate the functions of immune cells, leading to enhanced anticancer effects. This review mainly summarizes our current understandings of antitumor effect of gold drugs and their relationships with various aspects of antitumor immunity, including innate immunity, adaptive immunity, immunogenic cell death, and immune checkpoints, as well as their roles in adverse effects. Some recent examples of anticancer gold compounds are highlighted. The property of gold compounds is expected to combine with anticancer immunotherapy, such as immune checkpoint inhibitors, to develop new anticancer therapeutic strategies.